Revisão das espécies de Ancistrus Kner, 1854 (Siluriformes: Loricariidae) da bacia do rio Iguaçu, Paraná, Brasil, com descrição de três espécies novas. - Bifi, Alessandro Gasparetto (2008)
The genus Ancistrus is the most specious of the tribe Ancistrini, with 59 nominal species scattered over the Neotropical region, from Panama to middle portion of Argentina. In the Rio Iguaçu basin, that presents a high degree of endemism of ichthyofauna, specimens of that genus were caught and were attributed to three new species described herein following current methodologies. Ancistrus sp. A, Ancistrus sp. B, and Ancistrus sp. C are diagnosed from their congeners by having maxillary barbel short and not free from the lower lip, by lacking pre-anal-fin plate and also by morphomeristic analyzes. Ancistrus sp. A and Ancistrus sp. B are differentiated from Ancistrus sp. C by having a deeper occipital. Ancistrus sp. B and Ancistrus sp. C are diagnosed from Ancistrus sp. A by having a longer dentary. Comments on the geographic distribution of those species and congeners are also provided.